2013
DOI: 10.14260/jemds/705
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Hiv/Aids Patients: Occurrence and Risk Associated With Low Cd4 Counts.

Abstract: BACKGROUND:People living with HIV/AIDS with progressive immune dysfunction have an augmented risk of Urinary tract infection, both symptomatic and asymptomatic, in comparison to non-infected individuals. AIMS: This prospective study was planned to know the frequency of asymptomatic bacteruria (ASB) in HIV sero-positives and its correlation to their immune status. Conventional culture method was compared with screening test using SD Urocolor TM 10 test strips for the presence of infection. Antibiogram of isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…Our study has generated data for HIV- seropositive patients in this part of the country where information on bacteriuria among HIV- seropositive patients is scarce. When our findings was compared to those of other countries, the prevalence we recorded is higher than those observed in different parts of Nigeria (10.9% and 57.3), Ethiopia (9.2% and 11.3%), South Africa (37.6%)and India 3 , 4 , 10 , 14 16 . Our observation on female being more infected is consistent with almost all the studies we have come across 5 , 6 , 24 .…”
Section: Discussioncontrasting
confidence: 49%
“…Our study has generated data for HIV- seropositive patients in this part of the country where information on bacteriuria among HIV- seropositive patients is scarce. When our findings was compared to those of other countries, the prevalence we recorded is higher than those observed in different parts of Nigeria (10.9% and 57.3), Ethiopia (9.2% and 11.3%), South Africa (37.6%)and India 3 , 4 , 10 , 14 16 . Our observation on female being more infected is consistent with almost all the studies we have come across 5 , 6 , 24 .…”
Section: Discussioncontrasting
confidence: 49%
“…Multidrug resistance has serious implications on the health outcome of HIV-infected patients [9, 25]. It is quite alarming to note that almost 46% of the isolates in this study were found to be resistant to two or more antimicrobials.…”
Section: Discussionmentioning
confidence: 86%
“…The health consequences of UTI among HIV-infected patients can be grave, resulting in acute and chronic kidney diseases [7], infertility, cancer, sepsis, and neurologic complication, which lead to urinary stasis [8, 9]. Some of the patients may substantially suffer from financial burden not only because of the recurrence of UTI but also due to the use of expensive antimicrobials, longer duration hospitalization, adverse drug effects, and unsatisfactory therapeutic options [7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection is associated with a variety of renal syndromes; patients with low CD4 counts are at risk of the neurological complications of hyperreflexia and hyporeflexia which can lead to urinary stasis and ultimately infection. 7 The emergence of antibiotic resistance in the management of UTIs is a serious public health problem globally, particularly in the developing world. 8 Since bacterial pathogens of UTIs are variable regionally, infection control and treatment depend on local knowledge of common causative organisms and their antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%